2015
DOI: 10.1002/adma.201502070
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Processing of Nanocube Assemblies Toward Harvesting of a Metastable PbS Phase

Abstract: This materials-by-design approach combines nanocrystal assembly with pressure processing to drive the attachment and coalescence of PbS nanocubes along directed crystallographic dimensions to form a large 3D porous architecture. This quenchable and strained mesostructure holds the storage of large internal stress, which stabilizes the high-pressure PbS phase in atmospheric conditions. Nanocube fusion enhances the structural stability; the large surface area maintains the size-dependent properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
58
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 35 publications
3
58
1
Order By: Relevance
“…2c). The PL weakening should be ascribed to the deviatoric stress arising from the nonhydrostatic conditions in the diamond anvil cell (DAC), which was indeed reported in earlier studies using synchrotron radiation small-angle X-ray scattering 3133 . Deviatoric stresses eventually lead to slow amorphization of Cs 4 PbBr 6 NCs upon further compression, which is largely related to the higher degree of distortion and random orientations of inorganic octahedra within the material 25,34 .…”
Section: Resultssupporting
confidence: 55%
“…2c). The PL weakening should be ascribed to the deviatoric stress arising from the nonhydrostatic conditions in the diamond anvil cell (DAC), which was indeed reported in earlier studies using synchrotron radiation small-angle X-ray scattering 3133 . Deviatoric stresses eventually lead to slow amorphization of Cs 4 PbBr 6 NCs upon further compression, which is largely related to the higher degree of distortion and random orientations of inorganic octahedra within the material 25,34 .…”
Section: Resultssupporting
confidence: 55%
“…[2b,14] Coincidentally, the reversal pressure of ≈5 GPa was close to the orthorhombic‐to‐quasi‐amorphous transition pressure of 5.1 GPa. Thus, it is suggested that the atomic movement associated with phase transformation facilitated the detachment of ligands from the surfaces of NCs . When the pressure was reduced to ambient pressure, the d ‐spacing of the SAXS peak did not return to 12.6 nm; instead, it continuously increased to 14.3 nm (Figure B).…”
mentioning
confidence: 99%
“…Nanocrystals (NCs) respond specifically to pressure with respect to phase progression, coherent crystal domain size, particle agglomeration, and morphology, accompanied by physical and chemical property modification. For example, high pressure can induce distinct textural coalescence of metallic Au/Ag NCs along with tuning the corresponding plasmonic resonance; (meta)stable phases in conventional semiconductors including CdSe and PbS/Pt;[15a,16] and alternation in the carrier dynamics in CdTe NCs and CsPbBr 3 perovskite nanocube superlattices …”
mentioning
confidence: 99%